Using a Nonverbal Cognitive Abilities Screening Test in Identifying Gifted and Talented Young Children in Jordan: A Focus Group Discussion of Teachers*. (September 2019) - Alodat, Ali M.; Zumberg, Marshall F.
This qualitative study aimed to discover teachers' perceptions about the effectiveness of using the nonverbal Cognitive Abilities Screening Test (CogAT) in identifying gifted and talented children. The study's sample of six teachers participated in standardizing the Jordanian version of the CogAT. Teachers attended a focus group discussion, and they were asked to discuss four open-ended questions. The focus group discussion results indicated strong agreement by teachers of the effectiveness of using the Arabic Jordanian version of CogAT. Specifically, teachers expressed their satisfaction about the test items and guidelines. Moreover, they unanimously agreed that the test is appropriate to use in Jordan. Also, teachers provided many positive comments and feedback about the ability of this test to identify young gifted children. Finally, teachers described the reality of gifted education services in Jordan.